2021
DOI: 10.1111/cch.12883
|View full text |Cite
|
Sign up to set email alerts
|

Professionals' motivation to support parental self‐management regarding children with physical disability in Dutch rehabilitation services: ‘Please mind your gap’

Abstract: Background Professionals in child healthcare increasingly endorse the support of self‐management in paediatric rehabilitation services for children with physical disability. Less understood though are their views regarding the role of the children's parents, as well as their own role in supporting parents. This study aimed to investigate the motivation of rehabilitation professionals to support self‐management of parents regarding their child with physical disability, professionals' beliefs about parental self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…They found that around 90% of participants taking part in a mixed-methods study believed that parents should take an active role in their child's rehabilitation, whereas less than 10% considered parents taking the initiative and being independent actors in the rehabilitation process as being important. 53 The study additionally found that sharing responsibility could be difficult for professionals as they navigate maintaining authority and control with sharing responsibility with parents. This is echoed in the qualitative synthesis of literature carried out by Lord et al 54 relating to parent-delivered therapy interventions for children with cerebral palsy, which highlighted the need for support, trust, and shared decision-making in helping to build trusting relationships.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…They found that around 90% of participants taking part in a mixed-methods study believed that parents should take an active role in their child's rehabilitation, whereas less than 10% considered parents taking the initiative and being independent actors in the rehabilitation process as being important. 53 The study additionally found that sharing responsibility could be difficult for professionals as they navigate maintaining authority and control with sharing responsibility with parents. This is echoed in the qualitative synthesis of literature carried out by Lord et al 54 relating to parent-delivered therapy interventions for children with cerebral palsy, which highlighted the need for support, trust, and shared decision-making in helping to build trusting relationships.…”
Section: Discussionmentioning
confidence: 96%
“…Such approaches to coproduction will go some way in helping to address power imbalances and better support parent self-management. 53 Future research should also seek to provide detailed descriptions about the content of interventions and the underlying theory to provide rigour and transparency to the design process and enable the replication of interventions. 24 This will help to develop further evidence about parent-delivered rehabilitation and suggest which BCTs and elements of interventions are particularly important in supporting behavioural change.…”
Section: Strengths Limitations and Directions For Future Researchmentioning
confidence: 99%
“…The S‐scan ‐ PS should preferably be integrated within more extensive policies of healthcare institutes seeking to improve the delivery of family‐centred services. Importantly, such organisation‐wide strategies need to address the variety of expectations among the families they serve (Wong Chung et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, such organisation-wide strategies need to address the variety of expectations among the families they serve (Wong Chung et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation